From doubt to adoption: impact of a STEAM-based intervention on teachers’ perceptions and use of digital learning objects - Kostaki, Stela-Marina; Linardakis, Michalis (Journal of computers in education (the official journal of the Global Chinese Society for Computers in Education), 2025)
This article examines how a STEAM-based teaching intervention supported by Digital Learning Objects (DLOs) influenced primary school teachers’ preferences and attitudes toward ICT use in teaching. The intervention was designed based on the STEAM approach, implemented using the project method, and its activities focused on cultivating soft skills. The goal of the intervention was to familiarize teachers with a list of clearly defined characteristics of ICT-based teaching, which included three general characteristics: Grade level, Subject area of technology use, and the Interactive nature of digital resources; three teaching features of digital learning objects: Reusability, Generativity, and Adaptability; and four technical features of DLOs, namely Interoperability, Accessibility, Durability, and Interactivity. To explore the significance of these characteristics in primary school teachers’ choices to integrate digital resources into their teaching, Discrete Choice Models were employed to a sample of 102 participants. The analyses revealed a statistically significant increase in the influence of DLOs’ teaching and technical features on teachers’ preferences post-intervention. Regarding general characteristics, teachers continue to favor interactive resources, while differences between Subject areas disappear. Additionally, a UTAUT-based scale measured attitudes toward ICT, with Wilcoxon tests indicating significant improvements in four factors within the experimental group. The findings could inform the development of more suitable digital resources and targeted professional development programs for DLO integration. Moreover, the intervention’s methodology, structure, and content could serve as a model for future activities within Skills Workshops.